Use of high-fat diets to study rodent obesity as a model of human obesity - Speakman, John R (International Journal of Obesity, 2019)
At present there is a range of commercial high-fat diets available that have been demonstrated to make small rodents obese. However, some of these diets contain levels of dietary fat that are much higher than the levels that humans routinely consume. The question has been raised as to whether experimental use of these diets with very high levels of fat adequately models the situation of human obesity.